2018
DOI: 10.5152/iao.2018.4756
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Status in Patients with Benign Paroxysmal Positional Vertigo

Abstract: Our results suggest a role of oxidative stress in the development of BPPV, through both calcium metabolism and the direct toxic effects of free oxygen radicals, including the triggering of apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…Authors have demonstrated that NT levels were significantly lower in patients with benign paroxysmal positional vertigo, seasonal allergic rhinitis, Bell's palsy, obstructive sleep apne and nasal polyposis [53][54][55][56][57].…”
Section: Head and Neck Pathologiesmentioning
confidence: 99%
“…Authors have demonstrated that NT levels were significantly lower in patients with benign paroxysmal positional vertigo, seasonal allergic rhinitis, Bell's palsy, obstructive sleep apne and nasal polyposis [53][54][55][56][57].…”
Section: Head and Neck Pathologiesmentioning
confidence: 99%
“…In the present study, we found that there was significant difference in serum levels of SOD in the patients with BPPV before treatment vs. after treatment. However, one study found that the increase in oxidative stress did not respond to the treatments that were administered to patients with BPPV [17], and another study also showed that the levels of the antioxidant paraoxonase in patients with BPPV before and after treatment did not have obvious difference [19]. More further studies should be carried out to assess the role of treatment on the levels of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of inflammatory reaction and oxidative stress may play role in the occurrence of vascular vertigo and BPPV [15,17]. Several prior studies have explored the association between serum oxidative stress markers' concentrations and BPPV [19,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulated studies evidenced that the CSD is mainly triggered neuro-otologic and psychiatric disorders 13,19,20 . Furthermore, recent studies reported that the above pathological alterations are deeply related to the oxidative stress in clinical practice and animal based in vivo experiment [21][22][23] .…”
Section: Discussionmentioning
confidence: 99%